Estimation of food price-nutreint and nutrient-expenditure elasticities for Turkey - Dönmez, Neslihan (My University, 2019)
This study explores the effects of total food expenditure and food prices on nutrient intake in Turkey by estimating nutrient elasticities and aims to make an important contribution to the literature on nutrient demand. For this purpose, first, the Quadratic Almost Ideal Demand System (QUAIDS) is estimated for 12 food groups by using Turkish Household Budget Survey Data Set for the year 2003 in order to compute the expenditure and price elasticities. The expenditure elasticities for each food group are found to be positive, the own-price elasticities for each food group found to be negative; besides, all the demand elasticities are found to be statistically significant. In the second stage of the analysis, the nutrient values of the food groups are compiled from Türkomp National Food Composition Database to compute the nutrient shares in the food groups for selected 21 nutrient types. The obtained nutrient shares and the expenditure and own-price elasticities are used to estimate the expenditure-nutrient and food price-nutrient elasticities. It is found that an increase in total food expenditure increases the intake of all nutrients, and an increase in food prices reduces the intake of almost all nutrients. Since most nutrient types are provided from cereals, bread, meat and fish, dairy products, vegetables and fruits, increases in these food prices significantly affect most nutrients intakes. Finally, besides nutrient elasticities, the daily values of individual nutrient intake are calculated and compared with reference values. Results show that individual iodine, and vitamin A intakes are low while individual carbohydrate, protein, and sodium intakes are high for individuals. The most important finding in this analysis is that individual iodine intake is lower than the reference value and the increase in total expenditures does not have a large effect on iodine intake. Moreover, individual carbohydrate intake is found to be very high; however, a rise in total expenditure increases carbohydrate intake by one to one; hence, carbohydrate intake would be much higher. Likewise, changes in food prices also affect nutrient intake, but this effect is not large enough. Given all this, policies to be implemented on income and food prices may not produce desirable results for nutrient intake. The empirical findings of this study imply that income and food prices may not be effective policy tools for nutrient intake; therefore, the nutrition policy for improving individual nutritional status should be implemented considering all factors in addition to income and prices by policymakers.

Bu çalışmada Türkiye için besin esneklikleri hesaplanarak gıda fiyatlarının ve toplam gıda harcamalarının besin alımı üzerindeki etkileri araştırılmıştır ve bu çalışma ile besin talebi üzerine literatüre önemli bir katkı sağlanması amaçlanmıştır. Bunun için ilk olarak 2003 yılı Türkiye Hanehalkı Bütçe Anketi Veri Seti kullanılarak İkinci Dereceden Yaklaşık İdeal Talep Sistemi (QUAIDS) modeli 12 gıda grubu için tahmin edilmiş ve bu gıda grupları için harcama ve fiyat esneklikleri hesaplanmıştır. Ekonomik teoriye tutarlı olarak tüm gıda grupları için harcama esneklikleri pozitif, kendi fiyat esneklikleri negatif bulunmuş ve hepsi istatistiksel olarak da anlamlı çıkmıştır. Analizin ikinci aşamasında bu çalışmanın asıl konusu olan besin esnekliklerini hesaplamak için öncelikle 21 besin türü seçilerek tüketilen gıdaların besin değerleri Türkomp Ulusal Gıda Kompozisyonu Veri Tabanı’ndan derlenmiştir ve gıda grupları içindeki besin payları hesaplanmıştır. Besin payları ile birlikte gıda talebinden elde edilen harcama ve gıdaların kendi fiyat esneklikleri kullanılarak harcama-besin ve gıda fiyatı-besin esneklikleri hesaplanmıştır. Sonuçlara göre, toplam gıda harcamalarındaki artış tüm besin türlerinin alımını artırmaktadır ve gıda fiyatlarındaki artış ise neredeyse tüm besin türlerinin alımını azaltmaktadır. Besin türleri alımının çoğu tahıllar, ekmek, et ve balık, süt ve süt ürünleri, sebze ve meyve gıda gruplarından sağlandığı için bu gıdaların fiyatlarındaki artışlar hemen hemen tüm besin türlerinin alımını önemli ölçüde etkilemektedir. Son olarak, besin esnekliklerine ek olarak analize dahil edilen bireylerin günlük aldıkları besin değerleri hesaplanmış ve referans değerleri ile karşılaştırılmıştır. Sonuçlara göre bireylerin iyot ve A vitamini alımı düşük, fakat karbonhidrat, protein ve sodyum alımı yüksek çıkmıştır. Tüm bulgular göz önüne alındığında söyle bir sonuç çıkmaktadır; gelir üzerinden yapılacak politikalar beklenilen sonuçları veremeyebilir. Bu çalışmanın ampirik bulguları, gelir ve gıda fiyatlarının besin alımı için etkili politika araçları olamayacağı; bu nedenle, bireysel beslenme durumunun iyileştirilmesine yönelik beslenme politikası, politika yapıcılar tarafından gelir ve fiyatların yanı sıra tüm faktörler göz önünde bulundurularak uygulanmalıdır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Nutrient elasticities; Demand system; Household survey data; Food demand; Besin esneklikleri; Talep sistemi; Hanehalkı bütçe anketi verisi; Gıda talebi